Palisaded neutrophilic granulomatous dermatitis: Case report and review of literature - Bashair Ali Alzahrani; Anas Muwaffaq Tayeb; Johara Abdulkarim; Ruba Bahadur; Abdullah Almontashiri; Khalid Al Hawsawi (Wolters Kluwer Medknow Publications, 2020)
Palisaded neutrophilic granulomatous dermatitis (PNGD) is a rare inflammatory dermatosis. We report a 45-year-old female with a 2-year history of asymptomatic persistent skin lesions. The patient had rheumatoid arthritis well controlled with abatacept, methotrexate, and hydroxychloroquine. Multiple nonscaly umbilicated papules with crusted center were scattered on her abdomen, chest wall, and back. Biopsy showed pandermal infiltrate of neutrophils and areas of basophilic degenerated collagen surrounded by palisades of histiocytes, neutrophils deep in the dermis, and subcutaneous fat. A diagnosis of PNGD was made. The patient was treated with betamethasone dipropionate (0.05%) ointment and oral colchicine with good improvement.